Аbout some systemic problems of economic developmentin rural areas of Kazakhstan - Kunjazova, S.K.; Soltangazinov, A.R. (BUKETOV BUSINESS REVIEW, 2017)
This article deals with the systemic economic problems of rural areas of Kazakhstan. Purpose -The aim of the study is to identify the systemic economic problems of rural development and develop practical recommendations aimed at their solution. Methodology - based on the application of a functional-logical approach to the object under study, general scientific research methods: methods of comparison and generalization, abstractlogical and analytical. Originality/value - The main value of the work consists in the formulated conclusions and recommendations on the improvement of economic processes at the level of economic entities aimed at the rational and effective use of labor, land, material and other resources that enhance competitiveness and lean production. Findings - The economic basis for the development of rural areas is the agrarian sector, which occupies an important place in the structure of the rural economy and fulfills a systemic role in maintaining and developing the economic potential of these territories. The analysis of the economic structure shows the predominance of territories that have a dispersed production base, as well as the fact that personal subsidiary plots that occupy an independent place among other economic structures are an important sector of the rural economy. The research identified systemic economic problems and structural limitations of intensive growth of the rural economy, as well as recommendations for their solution. The authors developed recommendations and proposals that are of practical value and aimed at solving systemic problems and structural limitations of the intensive growth of the rural economy.